Addressing Health Disparities: Strategies for Achieving Health Equity in Low-Resource Setting - Srilalitha V, Srilalitha V; Kumar, B. Hema; Chakorkar, Snehal; Srudeepthi, Madupoju (Journal of Neonatal Surgery, 2025)
Health disparities in underserved communities represent an ongoing health issue because they lead to increased maternal fatalities as well as higher rates of infant mortality and they restrict access to basic healthcare services. The combination of economic barriers and poor infrastructure and cultural barriers and government failures creates complete inequality in healthcare service accessibility. A solution for this problem needs research-based policies and specific interventions to establish universal health equity. Health disparities reduction methods are studied by the investigation using studies of healthcare accessibility issues and current intervention evaluations to generate policy recommendations. The study incorporates both quantitative data from health surveys and secondary reports on international health as well as qualitative data extracted from successful programs dedicated to health equality. Health programs targeting communities in combination with universal healthcare developments and public-private alliances have shown to enhance healthcare services in disadvantaged areas. Health programs that have already been implemented need government support and dependable funding sources together with proper healthcare policy execution to succeed. The study evidence shows an urgent need to strengthen healthcare infrastructure by implementing telemedicine systems because this approach creates lasting health equity. The study provides essential information to policy administrators and healthcare providers and worldwide health programs about maintaining universal care through enduring long-term strategies.